COMPARING METAPHORS THAT MIDDLE SCHOOL AND HIGH SCHOOL STUDENTS’ POSSESS ABOUT THE CONCEPT OF ‘MATHEMATICS’ - Tuğba HANGÜL (Fırat University, 2019)
The main purpose of this study is to reveal the thoughts that middle school students’ and high school students’ possess about the concept of ‘Mathematics’ through metaphors and to compare these metaphors. The study was carried out together with 400 students in three public schools during autumn semester of 2012-2013 academic year. The research data was collected with the "Mathematics Metaphors Questionnaire" which prepared by the researchers. Questionnaire consists of two questions . The first question is "If mathematics was a type of food, it would be..... because ........... ", and the second question is "If mathematics was an animal, it would be..... because ........... ". It was asked students for writing a metaphor at first gap in the desired category about mathematics and also write the reason of selecting this metaphor at the second gap. Both content analysis and descriptive statistics were used for data analysis. Metaphors derived from the study were listed regardless of whether they were meaningful or not. In the next step, metaphors which were invalid removed from the list. Metaphors were grouped under five different categories accordingly having common characteristics in terms of the concept of "mathematics". These categories are “extent of mathematics”, "difficulty/ easiness/ nature of mathematics", "the necessity of mathematics" , "student interest / attitude", "teacher interest / attitude". At the end of the study, metaphors that students produced through mathematics were compared. Especially in the category of "extend of mathematics", high school students produced metaphors two times rate compared to middle school students. This situation can be associated with being more extensive of high schools mathematics curriculum compared to middle schools' mathematics curriculum.